The Role of Community Participation in Engineering Project Planning - Perdana, Ilham (Journal of Sustainability Industrial Engineering and Management System, 2025)
Community participation has emerged as a vital component in engineering project planning, particularly as projects become more complex and socially embedded. This research aims to explore the role of community participation in engineering projects by examining the extent, forms, and effectiveness of participation across different projects. The study adopts a literature-based qualitative approach, analyzing theoretical and empirical findings from various sectors, including water, transportation, and energy. By synthesizing studies from diverse geographical and socio-political contexts, the research seeks to identify patterns in how community participation influences project outcomes such as design relevance, social legitimacy, and long-term sustainability. The findings reveal that community participation, when meaningfully integrated into the early phases of planning, significantly enhances project outcomes by improving alignment with local needs, reducing conflicts, and ensuring greater project ownership. However, the research also identifies barriers such as knowledge asymmetry, institutional constraints, and social dynamics that limit the effectiveness of participation. These barriers often result in tokenistic participation rather than genuine engagement. Moreover, the study emphasizes the need for standardized measurement tools to assess participation and its impacts, suggesting that more systematic, data-driven approaches are required to bridge gaps in current research. Ultimately, this research contributes to a growing body of literature on participatory governance in engineering, offering both theoretical insights and practical recommendations for improving community engagement in planning processes. The study advocates for a shift towards a more inclusive model of engineering project planning that integrates community voices not only as stakeholders but as active co-creators of sustainable infrastructure solutions.